A Combinatorial Study of Photoelectrochemical Properties of Fe‐W‐O Thin Films. Issue 1 (24th November 2014) - Sliozberg, Kirill; Schäfer, Dominik.; Meyer, Robert; Ludwig, Alfred; Schuhmann, Wolfgang
Abstract: A continuous mixed Fe‐W‐O thin‐films materials library was fabricated by means of reactive co‐sputtering from elemental iron and tungsten targets in argon/oxygen. The materials library was screened for its local photoelectrochemical properties by using an automated optical scanning droplet cell. Local scanning electron microscopy (SEM) and electron‐dispersive X‐ray spectroscopy (EDX) measurements of the materials library were performed to correlate the composition, morphology, and photocurrents. The iron content was varied in the range from Fe32 W68 O x to Fe81 W19 O x . A strong dependence of the film morphology and the measured photocurrents on the composition was observed with a maximal photocurrent from a measurement area containing 55 at % iron. The most photoactive area showed a porous structure with a high surface area. The bandgap values of these materials were assessed by photocurrent spectroscopy and showed a systematic variation of the bandgap values with the composition. Abstract : Film library : The photoelectrochemical properties of compositions from a ternary Fe‐W‐O materials library strongly depend on the Fe/W ratio as well as the processing parameters. Photoelectrochemical screening was performed by using an automated optical scanning droplet cell on a continuous thin‐film materials library with a controlled gradient of compositions. The maximal photocurrent was obtained from a measurement area containing 55 at % Fe (see figure).